2015
DOI: 10.1038/bjc.2015.27
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 is an important prognostic and predictive factor for platin–pemetrexed therapy in malignant pleural mesotheliomas and deregulation of P14/ARF (encoded by CDKN2A) seems to contribute to an MDM2-driven inactivation of P53

Abstract: Background:Malignant pleural mesothelioma (MPM) is a highly aggressive tumour that is first-line treated with a combination of cisplatin and pemetrexed. Until now, predictive and prognostic biomarkers are lacking, making it a non-tailored therapy regimen with unknown outcome. P53 is frequently inactivated in MPM, but mutations are extremely rare. MDM2 and P14/ARF are upstream regulators of P53 that may contribute to P53 inactivation.Methods:A total of 72 MPM patients were investigated. MDM2 immunoexpression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 62 publications
1
23
0
1
Order By: Relevance
“…The prognostic significance of MDM2 overexpression is quite controversial in the literature [ 37 ]. We found a trend towards a negative prognostic and predictive significance of high MDM2 strong nuclear expression levels, thus confirming previous results in different case series [ 19 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The prognostic significance of MDM2 overexpression is quite controversial in the literature [ 37 ]. We found a trend towards a negative prognostic and predictive significance of high MDM2 strong nuclear expression levels, thus confirming previous results in different case series [ 19 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Few works have investigated the role of MDM2 expression in MPM and case series were represented mostly by epithelioid forms, thus making it difficult to draw any conclusion about different expression levels between the two main histologic subtypes [ 19 , 29 ]. Importantly, it was not clear if immunohistochemical and RT-qPCR analyses were performed on chemonaive samples, and no details about systemic and locoregional treatments of affected patients were reported, which might have some impact on survival data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we have demonstrated that MDM2 is overexpressed in approximately 20-30% of MPM and this finding was restricted to epitheloid MPM or the epithelioid components of biphasic MPM 78 , 79 . Moreover, patients with MDM2 -positive MPM presented with a significantly decreased OS compared to MDM2 -negative MPM 78 , 79 . The physiological inhibitor of MDM2 is P14/ARF and loss of P14/ARF activity may have a similar effect as loss of TP53 80 - 83 .…”
Section: Discussionmentioning
confidence: 84%
“…For example, one study reported that high levels of MDM2 expression correlated with poor survival in mesothelioma patients (86). Significantly, in a 2015 study, MDM2 has been shown to be an important prognostic and predictive marker for response to platin–pemetrexed therapy (antifolates and platin derivatives) in patients with malignant pleural mesothelioma (87). …”
Section: Mdm2 and Mdmx In Human Cancermentioning
confidence: 99%